A educação religiosa no Colégio Salesiano Sagrado Coração do Recife - Albuquerque, Danilo Araújo de (2014)
The Brazilian educational system is closely connected to the religiosity of its people. Education in the country was initiated by the Jesuits. The Salesians arrived in 1883 and brought to Brazil the preventive education system created by Don Bosco and whose foundations are the reason, religion and kindness. This education system aims to prevent young people destined to wrong paths, rather than waiting to punish them after erring. The first Salesian school in Brazil was inaugurated in 1883 in the city of Niterói, Rio de Janeiro. In 1895 was founded the Colégio Salesiano do Sagrado Coração. Even today with the crisis of values and the culture of death, the Salesian school maintains educational principles of Don Bosco. It inserts his students in the ecclesial community through Religious Education, which covers the various religions present in our society, the Catechesis that promotes youth evangelism and pastoral, that make the young multipliers Don Bosco s philosophy, forming good citizens from good Christians. The preventive system of Don Bosco remains an effective educational method but must be always updated, because nowadays just protect young people is not enough, we must teach them how to be protagonists of their lives with responsibility and Christian values to build a world most fair and equitable.